Challenging the links between microfinance and domestic violence: evidence from rural India. Issue 3 (2nd April 2020) - Yaron, Gil; Gordon, Rebecca; Best, John; Choudhary, Sunil
ABSTRACT: The impact of microfinance on domestic violence has been widely discussed, but there is still no consensus due to the fact that context and programme implementation mechanisms have a large effect on outcomes. An innovative grassroots microfinance organisation in India, Rojiroti, has a number of unique features which make a positive impact on domestic violence more likely. Using a quasi-experimental design with panel data and matched control sites, this article reports on a study that found a significant reduction in levels of domestic violence among women members of Rojiroti, alongside a significant increase in asset ownership and knowledge of household finances.